Interrelation of Diet, Gut Microbiome, and Autoantibody Production - Petta, Ioanna; Fraussen, Judith; Somers, Veerle; Kleinewietfeld, Markus (Frontiers in Immunology, 2018)
B cells possess a predominant role in adaptive immune responses via antibody-dependent and -independent functions. The microbiome of the gastrointestinal tract is currently being intensively investigated due to its profound impact on various immune responses, including B cell maturation, activation and IgA antibody responses. Recent findings have demonstrated the interplay between dietary components, gut microbiome and autoantibody production. ‘Western’ dietary patterns, such as high fat and high salt diets, can induce alterations in the gut microbiome that in turn affects IgA responses and the production of autoantibodies. This could contribute to multiple pathologies including autoimmune and inflammatory diseases. Here, we summarize current knowledge on the influence of various dietary components on B cell function and (auto)antibody production in relation to the gut microbiota, with a particular focus on the gut-brain axis in the pathogenesis of multiple sclerosis (MS).